Variations in Biochemical Parameters During Different Stages of Gestation in Pregnant Cows - Khiredine Metref, Ahmed; Aouane, Nedjma; Saidani, Khelaf; Yahia, Achour (The Indian Journal of Animal Reproduction, 2025)
The aim of this study was to determine the values of some metabolites, ions, and enzymes in maternal blood serum in relation to  gestation day in cattle. The maternal blood samples were collected. The cows were divided according to gestation months into four  groups: non pregnant, (n=26), under 3 months pregnancy (n=5), between 3- and 6-months pregnancy (n=4) and over 6 months  (n=5). Gestation had no statistically significant effect (P>0.05) in any of the studied groups. As pregnancy progresses,  maternal serum biochemical parameters underwent various changes. Glucose levels in pregnant cows showed a gradual  decrease until the final trimester of gestation. Similarly, cholesterol and triglyceride levels followed a decreasing pattern  before exhibiting a slight increase in the final trimester. Total protein levels demonstrated a gradual increase until the  final trimester in pregnant cows. Creatinine and urea values remained within normal limits across all study groups. In  terms of liver function parameters, only alkaline phosphatase (ALP) showed elevated levels above the reference range  during the last two trimesters of gestation. Finely, for electrolyte measurement no change revealed. The study of blood  parameters during pregnancy permits a useful tool that improves the accuracy of blood test interpretation in bovine  medicine.
Keywords: S e r u m Biochemical parameters; Pregnancy; Cows